Penerimaan Batas Kehidupan Berdasarkan Teks Sirah Nabawiyah - Ivandianto Ivandianto; Moh. Irtadji; Aji Bagus Priyambodo (Fakultas Psikologi Universitas Negeri Malang, 2021)
Erikson saw the frequent human experience of despair in the face of death or the limits of life. So it takes a new way of looking at death so that he can be accepted. This research uses the basic design of qualitative research of hermeneutic phenomenology gadamerian. The data obtained from the documentation of Sirah Nabawiyah text with the instrument of the researchers themselves. The conclusion is the acceptance of death can be done with the loyalty, love and concern for religion, Apostle and God, and by understanding the pure identity.